Health situation analysis of cervical cancer in Delhi - Sharma, Jyoti; Dhanasekaran, Kavitha; Yennapu, Madhavi (International Journal Of Community Medicine And Public Health, 2024)
The capital city of India, Delhi is endowed with a plethora of multi- and super-specialty hospitals, both private and government, for treating various diseases. Patients from around the globe seek medical care in Delhi. The primary healthcare system is robust, with a network of newly established Mohalla and polyclinics. However, when it comes to a sensitive disease, ‘cervical cancer’, all glorious claims mentioned above seem to be inadequate. Cervical cancer is the 2nd most common cancer among Delhi's females. Delhi was 1st state to launch HPV vaccination as a public health program in 2016 despite resistance from civil societies. A situation analysis from literature reveals that cervical cancer screening services at the primary and secondary levels are on the backburner in Delhi, which is also evident from the poor screening habits of Delhi's females (0.7%) according to NFHS-5. This prompts questions regarding organization of the cervical cancer prevention program (NP-NCD) and the delivery of screening services in Delhi. In this review we have tried to illuminate the contemporary landscape of cervical cancer burden, screening, and treatment, while also identifying opportunities for enhancing cervical cancer management in Delhi. The study finds that implementation research targeted at finding barriers in program organization and service delivery would help strengthen the capacity of Delhi’s health system.